Going for the gap: making the most of market opportunities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Liberalization offers greater opportunities for agricultural producers to market their products. But liberalization and changes in world trade regulations may also remove protection and support, leaving producers exposed to competition in an...